Proceedings of the 6th International Conference on Economics, Management, Law and Education (EMLE 2020) 2021
DOI: 10.2991/aebmr.k.210210.048
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Impact of Live Video Streaming on Customers’ Consumption Behavior and Intention

Abstract: Many merchants increasingly use live video streaming to sell their products to increase sales and promote their brands, which has created huge profits for them. Therefore, this paper will focus on customers' consumption behavior and intention on this platform. This research takes 50 people with shopping experience on living streaming platforms as the research object and adopts the research online questionnaires to analyze their consumption characteristics and consumption tendency. The results show that most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This prototype showcases the potential for voice user interfaces and voice commands in mobile applications. [4] In "Design and Implementation of a Voice-Based Navigation for Visually Impaired Persons," the authors used the Android Software Development Kit (SDK) to create a voice-controlled navigation system for visually impaired individuals. This system integrated Text-to-Speech (TTS) technology and Google Map API to enable voice-guided destination searches and route information.…”
Section: Literature Survey [1]mentioning
confidence: 99%
“…This prototype showcases the potential for voice user interfaces and voice commands in mobile applications. [4] In "Design and Implementation of a Voice-Based Navigation for Visually Impaired Persons," the authors used the Android Software Development Kit (SDK) to create a voice-controlled navigation system for visually impaired individuals. This system integrated Text-to-Speech (TTS) technology and Google Map API to enable voice-guided destination searches and route information.…”
Section: Literature Survey [1]mentioning
confidence: 99%
“…Ding et al [8] demonstrated the incremental value of live streams of restaurant kitchens to online food delivery (OFD) services, where the broadcasting of food safety information underpins user welfare benefits that far outweigh operational costs, fostering a positive consumer perception of food safety practices. According to Yang [9], respondents' most frequently purchased items through live-stream shopping are food products, followed by beauty products. Therefore, given the economic significance of online videos, understanding video consumption behavior is crucial for video platforms and marketers [10].…”
Section: Introductionmentioning
confidence: 99%